Functional expression and comparative characterization of four feline P450 cytochromes using fluorescent substrates. (2nd November 2017) - Okamatsu, Gaku; Kawakami, Kei; Komatsu, Tetsuya; Kitazawa, Takio; Uno, Yasuhiro; Teraoka, Hiroki
Abstract: 1. Cytochrome P450s (CYP) are a major group of metabolizing enzymes for xenobiotics in humans and other mammals. The properties of CYP isoforms in the domestic cat, an obligate carnivore, are largely unknown at present. In this study, we studied relative expression in tissues and enzymatic properties of nine significant feline CYP isoforms. 2. CYP2E2 transcript was most abundant in the feline liver, followed by CYP2A13 and 2E1. Transcripts of CYP3A131, 1A2 and 1A1 were also present in the liver, while CYP2D6 and 3A132 were only slightly expressed. CYP3A131 was a major transcript in the small intestine. 3. Four major CYP isoforms in the feline liver and small intestine (CYP1A2, CYP2A13, CYP2E2 and CYP3A131) were heterologously expressed in Escherichia coli to generate functional monooxygenase systems. We carried out screenings of 17 test compounds known to be inhibitors of CYP isoforms in other mammals as well as two anticancer drugs to assess the activity modulation of feline CYP isoforms using fluorogenic substrates. These CYP isoforms showed similar selectivity to counterparts in other mammals against inhibitors as a whole but with many exceptions. 4. The present study suggests the usefulness of the feline CYP recombinant system to obtain chemical affinity information and possible drug interactions in CYP metabolism of domestic cats.